2016
DOI: 10.1016/j.urolonc.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Prognosticators and outcomes of patients with renal cell carcinoma and adjacent organ invasion treated with radical nephrectomy

Abstract: Objective To study the natural history, prognosticators, and outcomes in patients with RCC with extension of tumor beyond Gerota’s fascia and/or invading contiguously into the adrenal gland (pT4). Patients and Methods From 1992 to 2012, we identified 61 patients who underwent radical nephrectomy and were found to have pT4 disease. Clinicopathological variables were queried using univariate analysis to identify relevant prognostic variables. Cox proportional hazards model was used for multivariate analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A single institutional study of 61 patients diagnosed with pT4 RCC undergoing RN found that preoperative LDH and ALP, M stage, pN stage, and sarcomatoid dedifferentiation were significantly associated with survival. 22 However, the aforementioned study was limited by a small cohort and it was also a single institutional review. In contrast, our findings were collected from a national multi-institutional database, possibly better reflecting real world data.…”
Section: Discussionmentioning
confidence: 99%
“…A single institutional study of 61 patients diagnosed with pT4 RCC undergoing RN found that preoperative LDH and ALP, M stage, pN stage, and sarcomatoid dedifferentiation were significantly associated with survival. 22 However, the aforementioned study was limited by a small cohort and it was also a single institutional review. In contrast, our findings were collected from a national multi-institutional database, possibly better reflecting real world data.…”
Section: Discussionmentioning
confidence: 99%
“…Another study carried out by Borregales et al. showed similar results ( 23 ), but the underlying mechanism needs to be further elucidated, which may be related to micro bone metastasis ( 14 , 24 ). Moreover, elevated ALP and AST mean liver damage and decreased coagulation function, creating a high potential of perioperative hemorrhage, and more careful hemostasis is required during the operation.…”
Section: Discussionmentioning
confidence: 81%
“…44,45 Tumour grade, local extent of the primary tumour, presence of nodal metastasis, and histological subtype are predictors of the disease relapse (Level of Evidence 3). 41,[46][47][48] As such, these variables should be noted because they contribute to important prognostic information.…”
Section: Prognostic Variablesmentioning
confidence: 99%